Numerical Study of Thermal and Resistance Characteristics in the Vortex-Enhanced Tube - Yiang Li; Wenzhi Cui; Xuefeng Jiang; Longjian Li; Juanfang Liu (Energies)
Heat transfer enhancement is always pursued in the industry to achieve high-performance and low-energy-consumption heat exchange devices and systems. For decades, various types of heat transfer-enhancing tubes with differing geometries and wall configurations have been developed. In this paper, the heat transfer and pressure drop characteristics of air inside an innovative heat transfer tube with regular wall dimples, namely a vortex-enhanced tube, which has a great application prospect in the gas–gas heat exchanger, are numerically studied with an experimentally validated model. The effects of the depth, axial pitch, and radial rotation angle of the dimple in the tube wall on the convective heat transfer coefficient and friction drag coefficient are comprehensively analyzed. Based on the Performance Evaluation Criteria (PEC) of the tubes, the optimal parameters of the vortex-enhanced tube are obtained. When Re ranges from 10,000 to 40,000, the comprehensive evaluation factor of the vortex-enhanced tube is 1.29 times higher than the smooth tube. Dimple pacing, dimple depth, and dimple helical angle of the optimal tube type are 8 mm, 6 mm, and 83°, respectively.